Encyclopedic Learning and Mastery of New Tools - Qiu, Panpan (Journal of Educational Research and Policies, 2025)
Under the background of the deep integration of knowledge explosion and digital technology, the traditional education paradigm with the core of subject and examination is facing severe challenges. Based on the philosophical thinking of the essence of education and the analysis of the realistic dilemma, this paper puts forward the dual core education concept of “encyclopedic learning” and “new tool Mastery”. The research shows that: providing broad knowledge stimulation in stages is the key path to stimulate individual potential, and the acquisition of “new tools” such as digital literacy and critical thinking is the survival cornerstone to control the information flood. The two endow each other, and point to the ultimate goal of education, which is to train modern citizens with freedom of thought, lifelong development and a better life.